Assest-backed securitization: practices in the Turkish banking sector and a proposal for securitization of problem credits - Saybaşılı, Rıfat Bilgitay (My University, 2002)
unknown
Keywords: Bankalar ve Bankacılık; Ekonomi; Finansman ekonomisi; Yatırım